Epigenetic Regulation of the TLR7 Gene and Its Correlation with Immune Dysregulation in Post-COVID Syndrome: TLR7 Gene and Its Correlation with Immune Dysregulation in Post-COVID Syndrome - Khalid, Beenish; Baig, Saeeda; Jafri, Aliya; Farrukh, Ghazala Masood; Nabeel, Sobia Khan; Faisal, Hina (Pakistan Journal of Health Sciences, 2025)
Toll-like receptor 7 (TLR7) is crucial for recognizing single-stranded viral RNA and initiating type I interferon signalling, which initiates antiviral immune responses. DNA methylation and other epigenetic controls may affect TLR7 expression and play a role in immune dysregulation in post-COVID syndrome. Objectives: To assess the association between immune dysregulation in people with post-COVID syndrome and epigenetic regulation of the TLR7 gene, specifically DNA methylation patterns. Methods: Patients with post-COVID-19 symptoms (≥12 weeks’ post-infection) and age- and sex-matched recovered controls participated in a case-control study. The purpose of peripheral blood mononuclear cells (PBMCs) was to use bisulfite pyrosequencing to analyze the DNA methylation of TLR7 promoter CpG sites, to use qRT-PCR to quantify TLR7 mRNA, and to use flow cytometry to immunophenotype immune cell subsets and type I interferon (IFN-α) production. Analysis was done on statistical relationships among immune parameters, gene expression, and methylation status. Results: In comparison to controls, post-COVID patients showed notable changes in TLR7 promoter methylation patterns, with site-specific hypo- and hyper-methylation associated with corresponding changes in TLR7 expression. Anomalies in B-cell and plasmacytoid dendritic cell (pDC) profiles and dysregulated IFN-α levels were linked to aberrant expression, suggesting persistent innate immune activation. Conclusions: TLR7 epigenetic changes could be a factor in post-COVID-19 persistent immunological dysregulation. These results emphasize TLR7 methylation as a possible therapeutic target and biomarker. To confirm these correlations, more long-term research is needed.